2012
DOI: 10.5334/jbr-btr.75
|View full text |Cite
|
Sign up to set email alerts
|

The accessory spleen: prevalence and imaging findings in 1735 consecutuve patients examined by multidetector CT

Abstract: Accessory spleens represent congenital variants of small isles of normally encapsulated splenic tissue with its own arterial and venous vascularisation and their prevalence seems to range between 10 and 20% (1-5). Accessory spleens do undergo the same pathophysiological mechanisms as the main spleen and, therefore, they may show all the potential lesions that may be observed in the main spleen, ranging from shrinking to swelling, from calcification to cyst or tumor formation and from haemorrhage to infarction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…In addition, the maximum length of accessory spleen was more than that in American people. Romer and Wiesner studied CT-examination of 1735 patients in Switzerland, the accessory spleen was found in 11% of patients (8). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the maximum length of accessory spleen was more than that in American people. Romer and Wiesner studied CT-examination of 1735 patients in Switzerland, the accessory spleen was found in 11% of patients (8). …”
Section: Discussionmentioning
confidence: 99%
“…In the USA, the incidence of accessory spleen was found at autopsy in 10-30% of American population (4). In a European study was found that the accessory spleen was present in 11% of patients undergoing abdominal CT-scan (8). The incidence of accessory spleen ranged between 4.5% and 24.28% in Asian population (9-11).…”
Section: Introductionmentioning
confidence: 99%
“…AS can be encountered on CT in 11.0-18.8% of cases [3,4]. In up to 40% of these cases, the patient has two or more (up to four) AS [4].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% are found at the splenic hilum and 33% at the lower pole of the spleen 2. Other locations of accessory spleens, although more rare, include the fundus of the stomach,3 pancreatic tail,4 greater omentum,5 retroperitoneum6 7 and pelvis 8…”
Section: Introductionmentioning
confidence: 99%